Correlation of Hand Dominance and Body Mass Index on Maximal Isometric Handgrip Strength among Students of SKIMS Medical College, Srinagar, India - Mumtaz Gowhar; Farhana Ahad; Javed Hussain Bhat (National Journal of Medical Research)
Background: Handgrip strength (HGS) serves as an essential indicator of overall muscular strength and is influenced by factors such as Body Mass Index (BMI). This study examines the relationship between BMI and HGS in both dominant and non-dominant hands and investigates potential gender differences in these associations.